Tariff Analytical and Simulation Tool for Economists (TASTE) - Horridge, Mark; Laborde Debucquet, David (International Food Policy Research Institute, 2009)
The TASTE program has been designed to allow a large number of users to analyze existing trade policies and perform tariff scenarios. It is based on the MAcMap-HS6 database (version 2, baseyear 2004). It addresses several needs: (1)Queries on the MAcMap-HS6 database and computation of aggregate tariffs (bound and applied) at different sectoral and regional level (different aggregation methods allowed); (2)Simulations of tariff changes resulting from a trade policy scenario implemented at the product (HS6) level. Outputs can be used in different models and for instance, the integration in runGTAP is straightforward; and (3)Disaggregation tools for GTAP users in combination with the SPLITCOM software. TASTE comes with a huge database of bilateral trade flows and of applied and bound tariff rates distinguishing around 200 countries and 5000 HS6 goods. This data, based on a number of sources, has been processed by David Laborde. The trade flows are consistent with Version 7 of the GTAP database. The current version of TASTE uses the MAcMApHS6 version 2 data, and is designed to accompany the version 7 GTAP database. The TASTE program itself reads the enormous dataset and performs various operations using optimized routines, in particular:(1) Computing aggregated tariffs; (2) Transformation of scenarios about formula-based changes in bound rates into files of percent change shocks to applied rates -- which could be used by different models such as RunGTAP; (3) Generation of matrices of splitting weights which could be used to split a sector in the trade matrices of a GTAP model database (maybe using the SplitCom method).